PERDEBATAN ASPEK-ASPEK KETUHANAN DALAM TEOLOGI ISLAM DAN KAITANNYA DENGAN KALIMAT TAUHID(Analisis Terhadap Tiga Mazhab Besar Teologi Klasik; Mu’tazilah, Asyariyah dan al- Maturidiyah) - Abdul Wahab Syakhrani (CV. Adiba Aisha Amira, 2023)
Belief in God is a belief that has existed throughout human civilization. This belief is a human instinct, every human being must believe in the existence of God. This can be seen from historical and anthropological evidence, however, perceptions about the essence of God are different. Primitive humans, for example, believed in objects that had a mysterious and awesome impression. This fact shows the existence of divine potential in human beings. The mutakkallimin debate on the aspect of divinity which gave rise to debates in the history of Islamic theology in relation to the sentence of monotheism spurred the paradigm of the Muslim ummah in responding to various developments, and became a solid building in understanding the essence of divinity and the oneness of God. If we look at some of the literature on Islamic theology, at least we can conclude that the many schools of Islamic theology that have emerged are caused by several factors. First, various understandings of one verse in the Koran and the hadith of the Prophet Muhammad. The second is the expansion of the Muslim community which causes a mix-up between Islam and other ideologies. The third is the process of translating philosophical works into Arabic, and finally the fourth is the heating up of political and economic temperature among Muslims. In theology itself for example, with emergence of such debate Muslims can prove that Belief in Islam is not just a context and blind obedience to religious doctrine but can be approached through a ratio and approach systematic thinking. In connection with the existing divinity debate relation to the sentence of monotheism, at least Islam refers to several streams which is constantly referenced in this debate. Namely the Mu'tazilah, Ash'ariyah and Maturudiyah.